ANALISIS FAKTOR PENYEBAB KETERLAMBATAN PROYEK KONSTRUKSI GEDUNG - Violita Ananda; Ely Mulyati (Ensiklopedia of Journal, 2026)
This study aims to analyze the factors that cause delays in the construction project of the Convention Hall Building at Politeknik Pariwisata Palembang. Construction project delays are common problems that can affect cost, quality, and project performance. This research employed a quantitative approach using primary data collected through questionnaires distributed to 41 respondents consisting of contractors, construction management, and related stakeholders. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS) with SmartPLS software. The results show that several factors significantly influence project delays, including labor, material, equipment, design, planning and implementation, financing, social environment, and managerial aspects. Among these variables, managerial and design factors were identified as dominant contributors to project delays. The findings of this study are expected to provide insights for project stakeholders in improving project management and minimizing construction delays in future projects